Myanmar Economic Monitor, January 2022 : Contending with Constraints - World Bank (World Bank, Washington, DC, 2022)
Myanmar’s economy continues to be severely tested by the ongoing impacts of the military coup and the surge in COVID-19 cases in 2021. While some real-time indicators have improved in recent months, they remain consistent with a much lower level of economic activity than prior to the February coup. Reported COVID-19 cases have fallen to low levels (and few reported cases of the Omicron variant as of early January 2022), while real time indicators of mobility, manufacturing activity, and exports are showing signs of recovering. On the other hand, indicators of conflict suggest that the security environment has deteriorated in many parts of Myanmar, including in states and regions which have historically been relatively peaceful. This has affected businesses’ operations, logistics, confidence, and appetite to invest. After the sharp decline in incomes and employment observed across the economy, available indicators suggest domestic demand remains very weak. At the same time, supply-side constraints persist and some have worsened in recent months. Access to kyat liquidity, credit, and foreign currency remains severely constrained. A sharp exchange rate depreciation in September 2021 has raised import prices across the economy, including of fuel and other critical inputs to production, increasing transport costs. Electricity outages are a growing concern and internet disruptions continue to reduce the reliability of firms’ and households’ connectivity and ability to access information and connect with markets (see Part III: Digital Disruptions and Economic Impacts).